ROLE OF CORPORATE SECURITIES IN CAPITAL MARKET (American Journal of Business Management, Economics and Banking, 2025)
This article studies role of corporate securities in capital market. Moreover, types and forms of corporate securities, some aspects of different securities are analyzed in detail. Scientific conclusions and recommendations are presented on the basis of analyses.